Supervisor-Subordinate (Dis)agreement on Ethical Leadership: An Investigation of its Antecedents and Relationship to Organizational Deviance. Issue 1 (11th September 2018) - Kuenzi, Maribeth; Brown, Michael E.; Mayer, David M.; Priesemuth, Manuela
ABSTRACT: We examine supervisor-subordinate (dis)agreement regarding perceptions of the supervisor's ethical leadership and its relationship to organizational deviance. We find that, on average, supervisors rate themselves more favorably on ethical leadership compared to how followers rate them. In addition, polynomial regression results reveal that unit-level organizational deviance is higher when there is agreement about lower levels of ethical leadership, and disagreement when supervisors rate themselves higher on ethical leadership than subordinates' ratings of the supervisors. Finally, drawing on social influence theories, we look at antecedents of (dis)agreement and find that supervisors' beliefs about themselves (that they were "better-than-average" ethical leaders) and others (their assumptions about whether the morality of their subordinates is malleable or not) are associated with self-other (dis)agreement on ethical leadership.